The Genome Sequence of a Reassortant Bluetongue Virus Serotype 3 from India - Maan, Narender S. (American Society for Microbiology, 2012)
All 10 genome segments (Seg-1 to 10—a total of 19,188 bp) were sequenced from a strain of bluetongue virus serotype 3 (BTV-3) from India (strain IND2003/08). Sequence comparisons showed that nine of the genome segments from this virus group with other eastern topotype strains. Genome Seg-2 and Seg-6 group with eastern BTV-3 strains from Japan. However, Seg-5 (the NS1 gene) from IND2003/08 belongs to a western lineage, demonstrating that IND2003/08 is a reassortant between eastern and western topotype bluetongue viruses. This confirms that western BTV strains have been imported and are circulating within the subcontinent.